Intervensi pemilihan penolong persalinan pada ibu hamil trimester 3 - Sari, Kirana Candra; Nurrasyidah, Nurrasyidah; Rodiah, Dina (Holistik Jurnal Kesehatan, 2025)
Background: Maternal mortality remains a major health problem in Indonesia, influenced by the choice of delivery attendants. Interventions through structured health education are expected to improve maternal knowledge, attitudes, and decision-making in choosing safe delivery attendants. Purpose: To analyze the influence of interventions on the selection of birth attendants on pregnant women in the third trimester. Method: A cross-sectional study using a one-group pre-posttest method was conducted from January to August 2025 at the Padarincang Community Health Center, Banten. The sampling technique used purposive sampling with a sample size of 50 respondents. The independent variable in this study was birth attendants, while the dependent variable was pregnant women. Data analysis used univariate in the form of frequency distribution and bivariate using the Paired T-Test. Results: The educational intervention had a significant impact on increasing knowledge, attitudes, and decisions regarding the selection of birth attendants. The average knowledge score increased from 12.8 ± 2.4 in the pre-test to 16.7 ± 2.1 in the post-test (p = 0.000). Attitude scores also increased from 38.5 ± 0.6 to 45.3 ± 4.9 after the intervention (p = 0.000). The decision to choose a health worker as a birth attendant increased from 3.1 ± 0.7 to 4.5 ± 0.5 (p = 0.000). Conclusion: Educational interventions are proven effective in increasing knowledge, shaping positive attitudes, and strengthening decisions of pregnant women to choose health workers as delivery attendants.   Keywords: Attitude; Childbirth; Knowledge; Pregnant Women; Trimester 3.   Pendahuluan: Angka kematian ibu masih menjadi masalah kesehatan utama di Indonesia, salah satunya dipengaruhi oleh pemilihan penolong persalinan. Intervensi melalui edukasi kesehatan terstruktur diharapkan mampu meningkatkan pengetahuan, sikap, dan keputusan ibu hamil dalam memilih penolong persalinan yang aman. Tujuan: Untuk menganalisis pengaruh intervensi pemilihan penolong persalinan pada ibu hamil trimester 3. Metode: Penelitian cross-sectional dengan metode one group pre-posttest, dilaksanakan pada bulan Januari-Agustus 2025 di Puskesmas Padarincang, Banten. Teknik pengambilan sampel menggunakan puposive sampling dengan jumlah sampel yang digunakan sebanyak 50 responden. Variabel independen dalam penelitian ini adalah penolong persalinan, sedangkan variabel depeden ialah ibu hamil. Analisis data yang digunakan univariate dalam bentuk distribusi frekuensi dan bivariate menggunakan Paired T-Test. Hasil: Intervensi edukasi memberikan dampak yang signifikan terhadap peningkatan pengetahuan, sikap, dan keputusan pemilihan penolong persalinan. Rata-rata skor pengetahuan meningkat dari 12.8 ± 2.4 pada pre-test menjadi 16.7 ± 2.1 pada post-test (p = 0.000). Skor sikap juga mengalami peningkatan dari 38.5 ± .6 menjadi 45.3 ± 4.9 setelah intervensi (p = 0.000). Keputusan pemilihan penolong persalinan tenaga kesehatan meningkat dari 3.1 ± 0.7 menjadi 4.5 ± 0.5 (p = 0.000). Simpulan: Intervensi edukasi terbukti efektif dalam meningkatkan pengetahuan, membentuk sikap positif, dan memperkuat keputusan ibu hamil untuk memilih tenaga kesehatan sebagai penolong persalinan.   Kata Kunci: Ibu Hamil; Pengetahuan; Persalinan; Sikap; Trimester 3.